Peran Sarjana Pendamping Penggerak Pembangunan Olahraga (SP3OR) dalam Meningkatkan Partisipasi Masyarakat pada Kegiatan Olahraga di Kabupaten Subang - Sopyan Rizky Haryadi; Arif Fajar Prasetiyo (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to analyze the role of the Sports Development Facilitator (SP3OR) in increasing community participation in sports activities in Subang Regency. This research uses a descriptive qualitative approach with data collected through interviews, observations, and documentation. The research informants consisted of SP3OR, village officials, sports community administrators, and community members participating in sports activities. The results show that the presence of SP3OR significantly increased community participation from 42% to 71%. SP3OR acts as a motivator, facilitator, and community empowerment agent capable of organizing sports activities and establishing and strengthening sports communities. The facilitation program was considered effective by the community with an average score of 4.18 on a scale of 1–5. This study concludes that SP3OR plays a strategic role in developing a community-based sports culture and recommends continuous collaboration among the regional government, SP3OR, and the community to ensure the sustainability of sports activities in Subang Regency.